Efficacy of Albendazole and Short-Course Prednisolone Treatment in Children with One or Two Ring-Enhancing Lesions of Neurocysticercosis: A Randomized Controlled Trial - Swain, PK; Thapalial, A; Das, RN; Dhaliwal, MS; Subedi, K (Journal of Nepal Paediatric Society, 2009)
<!–[if gte mso 9]> mother 11.6568 <![endif]–><!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Context: Neurocysticercosis is a endemic disease in Nepal causing social and financial burden on society and developmental problem in children. Aims: To determine the efficacy of albendazole plus oral prednisolone in children with 1 or 2 ring-enhancing lesions (by CT) on resolution of lesions and recurrence of seizure. Setting and Design: Randomized controlled open trial. Methods and Materials: Children with 1 or 2 ring-enhancing lesions < 20 mm in diameter on computed tomography scan, likely to have Neurocysticercosis, were assigned to treatment & control groups. Children assigned to the treatment group (n = 50) were given 2.0 mg/kg per day prednisolone orally for 5 days plus 15 mg/kg per day albendazole on third day for 28 days. Anti epileptic drugs were given to both groups including Control group (n = 51). Statistical Analysis: The results were analysed with the use of Epi Info version 6.04 and Stata version;7 software. Results: The lesions resolved completely or partially in more children in the treated group compared with the control group (p = .04 & p = 0.03). The proportion of children who had seizures was significantly lower in the treated group compared with the control group at 6 months (10% versus 33%; p = .006) and 12 months (14% versus 38%; p = .003). Conclusion: Albendazole plus Prednisolone increased resolution of lesions on computed tomography scan and reduced the risk of subsequent recurrence of seizures among children with Neurocysticercosis. Key words: Prednisolone, Albendazole, Neurocysticercosis and Children. doi:10.3126/jnps.v27i2.1410 J. Nepal Paediatr. Soc. Vol.27(2) p.60-63